The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1423-0127-21-31
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of enterovirus 71 infection: applications and limitations

Abstract: Human enterovirus 71 (EV71) has emerged as a neuroinvasive virus that is responsible for several outbreaks in the Asia-Pacific region over the past 15 years. Appropriate animal models are needed to understand EV71 neuropathogenesis better and to facilitate the development of effective vaccines and drugs. Non-human primate models have been used to characterize and evaluate the neurovirulence of EV71 after the early outbreaks in late 1990s. However, these models were not suitable for assessing the neurovirulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 86 publications
4
49
0
Order By: Relevance
“…Previously, single mutations (G145E, E145Q, and K244E) in the conserved, positively charged 5-fold region of the VP1 capsid protein were identified as important sites for mouse adaptation of EV71 (13,14). Those studies used very young, 2-week-old ICR and 5-day-old BALB/c mice and also 3-to 4-week-old immunocompromised NOD/SCID mice (13,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, single mutations (G145E, E145Q, and K244E) in the conserved, positively charged 5-fold region of the VP1 capsid protein were identified as important sites for mouse adaptation of EV71 (13,14). Those studies used very young, 2-week-old ICR and 5-day-old BALB/c mice and also 3-to 4-week-old immunocompromised NOD/SCID mice (13,14).…”
mentioning
confidence: 99%
“…Those studies used very young, 2-week-old ICR and 5-day-old BALB/c mice and also 3-to 4-week-old immunocompromised NOD/SCID mice (13,14). However, the mechanism by which these changes contribute to adaptation remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed a range of EV71 infections in mice, from asymptomatic to severe. Before our studies, adult BALB/c mice were considered resistant to EV71 infection (9). However, we demonstrated that these mice had relatively high viral loads in many tissues and serum and expressed luciferase for several weeks after being infected with mEV71-NLuc.…”
Section: Figmentioning
confidence: 99%
“…Epidemiological surveys, ethical considerations and economic analyses are required to further support the rationale for a multivalent HFMD vaccine. The lack of appropriate animal models has so far been a hurdle in the evaluation of vaccine potency [22]. The use of chimpanzees is prohibited for both ethical and financial reasons but the engineering of transgenic mice expressing the EV71/CVA16 SCARB2 receptor represents a very promising approach in future pre-clinical studies [23].…”
mentioning
confidence: 99%